A new versatile active element and its application in design of minimum component all pass filters - Sampe, Jahariah; Faseehuddin, Mohammad; Hamid Md Ali, Shawal (International Journal of Engineering and Technology, 2018)
In this paper a new active block namely Dual X current conveyor differential input transconductance amplifier (DXCCDITA) is discussed. A first order current mode (CM) Single Input Multi Output (SIMO) universal filter and four structures of all pass filters are developed using single DXCCDITA. Each of the proposed filters require only a single active element and minimum number of passive components one/three for implementation. The designed SIMO filter uses only one resistor and one capacitor both are grounded. Furthermore, one of the designed all pass filter uses only one grounded capacitor and enjoys cascadeability and independent tunability of pole frequency. The effect of non-idealities on the proposed filter topologies is also studied. The DXCCDITA is implemented in 0.35μm TSMC CMOS technology parameters and tested in Tanner EDA. Sufficient number of simulations are provided to establish the functionality of the proposed structures.